Airway Papillomatosis: New Treatments for an Old Challenge - Kumar, Nankee; Preciado, Diego (Frontiers in Pediatrics, 2019)
Recurrent respiratory papillomatosis (RRP) is the recurrent growth of small, benign tumors, or papillomas, in the respiratory tract, caused by human papillomavirus (HPV). Currently, there is no cure. Palliative treatments seek to prevent airway obstruction, keep underlying tissues healthy, and maintain voice quality. The most common intervention, the local surgical removal of papillomas, may be inappropriate as a standalone treatment for pediatric populations that experience rapid papilloma regrowth, as repeated surgeries cause increased damage to the surrounding tissues and impose significant emotional and economic burden on families. Interferon α and Cidofovir have been shown to lengthen the time between surgical interventions and/or decrease the total number of procedures needed, although the evidence of their efficacy and safety is controversial. Novel therapies, including photodynamic therapy, indole-3-carbinol, anti-reflux medication, heat shock protein, and Mumps and HPV vaccination, may provide potential avenues for treatment, but require further research. Among all the novel therapies investigated, systemic bevacizumab seems to offer the most promising alternative to surgery. Randomized control trials to investigate its impact, especially in a pediatric population, should be conducted before implementing it as a standard form of care. This review will summarize the latest literature on medical care for aggressive RRP disease.